Trans-gastric and trans-abdominal percutaneous drainage of acute peripancreatic fluid infected collections: A retrospective analysis. (July 2022) - Rey, Carlos; Conde, Danny; Girón, Felipe; Ayala, Daniela; Gonzalez, Juliana; Melo, Daniela; Quintero, Marco
Abstract: Background: Acute pancreatitis is one of the most common gastrointestinal diseases. Approximately 20% of the patients develop peripancreatic collections. Step-up management it's now the best approach with less rate of morbidity and mortality compared with open or minimally invasive surgery. Percutaneous management could reach a success rate between 50 and 76%. Our study shows the outcomes of trans -gastric versus transabdominal percutaneous drainage in cases of acute peripancreatic fluid infected collections in the absence of interventionist endoscopy. Methods: A retrospective review of a prospectively collected database was conducted. All the patients older than 18 years old that underwent percutaneous drainage between January 2010–December 2021 were included. Analysis and description of outcomes such as mortality, complications, and avoidance of surgical procedures was performed. Results: 18 patients underwent percutaneous drainage. 66.67% of patients were male. Mean age was 52.55 ± 22.06 years. Mean weight was 74.43 ± 15.25 kg. Mean size of peripancreatic collections 118.4 ± 49.12 mm. Wall-off necrosis was present in 33.33%. Trans -gastric approach was performed in 50% of the cases, the rest was trans -abdominal. No mortality was evidenced after 30 days of follow up. After trans -gastric percutaneous drainage, all patients avoided surgical open or laparoscopic procedure. Conclusion: Standardized step-up approach shows increased rates of success in percutaneous drainage of peripancreatic collections. Our case series shows a high rate of success in terms of avoidance any surgical procedure with no mortality after trans -abdominal and trans -gastric percutaneous drainage. Nevertheless, further prospective studies with higher sample size are needed. Highlights: Trans -gastric and trans -abdominal percutaneous drainage of peripancreatic infected collections are safe and feasible procedures. In cases of no access to interventional endoscopy, percutaneous drainage remains to be a safe procedure. Multidisciplinary approach leads to good outcomes with less rate of morbidity and mortality.